NMR characterization of the conformational fluctuations of the human lymphocyte function‐associated antigen‐1 I‐domain. (5th September 2014) - Leung, Hoi Tik Alvin; Kukic, Predrag; Camilloni, Carlo; Bemporad, Francesco; De Simone, Alfonso; Aprile, Francesco A.; Kumita, Janet R.; Vendruscolo, Michele
Abstract: Lymphocyte function‐associated antigen‐1 (LFA‐1) is an integrin protein that transmits information across the plasma membrane through the so‐called inside‐out and outside‐in signaling mechanisms. To investigate these mechanisms, we carried out an NMR analysis of the dynamics of the LFA‐1 I‐domain, which has enabled us to characterize the motions of this domain on a broad range of timescales. We studied first the internal motions on the nanosecond timescale by spin relaxation measurements and model‐free analysis. We then extended this analysis to the millisecond timescale motions by measuring 15 N‐ 1 H residual dipolar couplings of the backbone amide groups. We analyzed these results in the context of the three major conformational states of the I‐domain using their corresponding X‐ray crystallographic structures. Our results highlight the importance of the low‐frequency motions of the LFA‐1 I‐domain in the inactive apo‐state. We found in particular that α‐helix 7 is in a position in the apo‐closed state that cannot be fully described by any of the existing X‐ray structures, as it appears to be in dynamic exchange between different conformations. This type of motion seems to represent an inherent property of the LFA‐1 I‐domain and might be relevant for controlling the access to the allosteric binding pocket, as well as for the downward displacement of α‐helix 7 that is required for the activation of LFA‐1.